Involving Digital Natives in Universities’ Extracurricular Offer and Social Activities - Monika SADY; Agnieszka ZAK (Communications of International Proceedings, 2021)
University’s extracurricular offer in the field of social responsibility gives students the opportunity for social engagement and competences development. It is especially important for the representatives of digital natives generation, who are future professionals, as well as political and social leaders, and therefore should be educated in a multidisciplinary and interdisciplinary way in order to anticipate, prevent, and resolve the problems of the society of the future. Through responsible education, higher education institutions enable transformation of existing paradigms and introduce the principles of social responsibility in all spheres of functioning of societies and individual units. The main objective of this study is to analyze how universities in Poland shape students’ competences in terms of social awareness and social engagement. The research was conducted from two perspectives: university and students. Socially responsible activities offered by 23 Polish public universities were inspected, and 261 students took part in a conducted questionnaire investigating whether digital natives engage in additional university and non-university activities, if they provide information about additional social activities undertaken during studies in their CVs, and if that information is of interest to the recruiters during job interviews.
Keywords: University; Students; Digital Natives; Social Responsibility